Six-parameter electrical model for photovoltaic cell/module with compound parabolic concentrator. (1st November 2016) - Li, W.; Paul, M.C.; Sellami, N.; Sweet, T.; Montecucco, A.; Siviter, J.; Baig, H.; Gao, M.; Mallick, T.; Knox, A.
Highlights: A six-parameter electrical model for a PV cell/module with CPC is presented. Importance of each parameter is analysed through a robust sensitivity algorithm. Scaling law is proposed for a PV cell with CPC operating under outdoor climate conditions. Transient performance is examined by coupling optical, thermal and electrical effects. Abstract: It is known that compound parabolic concentrators (CPCs) can improve electrical performance of a photovoltaic (PV) flat-plate system. However, a lumped electrical model of a PV cell/module with CPC for assessing performance under different operating conditions is unavailable. In this paper, a six-parameter based model is developed and applied to a PV cell, two PV models with CPC, and a PV module with 2D asymmetric CPC (trough). For validation, CPC with a single PV cell and two CPC modules with 2 × 2 and 9 × 9 PV cells are fabricated and measured in an indoor laboratory under standard test conditions. Results show that the optimised algorithm precisely predicts the six model parameters. A sensitivity analysis is performed to identify the importance of each parameter in the model. Ideality factor, circuit current and reverse saturation current are found to be the most dominant factor, while shunt resistance is the least important with CPC gain coefficient and series resistance are in between. Transient performance of a PV cell with CPC under variable outdoor climate conditions is also examined by coupling optical, thermal and electrical effects.